3D antenna arrays design for WPT systems - Pires, Diogo Rafael Pinto (2020)
The emerging concept of the Internet of Things (IoT) networks and smart cities, together with the constant innovation of wireless communications systems, presents a fundamental requirement, which is the capability of tracking, establish and maintain radio links with several targets, which can or can not be in motion. These demands results in the need to develop antennas capable of robust tracking and realize a full azimuth coverage. This dissertation focuses on the development and behavior characterization of different Three-Dimensional (3D) antenna arrays structures. The purpose of this alternative design comes from the advantages that it can bring in applications that would benefit from the possibility of having an antenna with considerable gain, capable of transmitting/receive signals or energy to/from all directions. However, the main goal of this dissertation consists on evaluating the viability of these antenna arrays implementation in Wireless Power Transmission (WPT) systems, with the primary goal of feed passive or low-power sensors, which can be scattered over a wide area. In order to obtain a functional system, the conceived 3D arrays will be fabricated and tested in phases. First, it will be necessary to design and test individually, the antennas that will constitute the array. Then, to study the overall array characteristics, simulations will be performed. Lastly, measurements will be performed in the prototyped 3D antenna arrays. A setup system that intends to simulate a Wireless Sensor Network (WSN) will be used. The developed antenna arrays have proven to be a reliable solution if implemented in these systems, since they are able to ensure a full azimuth coverage and so, feed passive or low-power sensors, regardless of their position over the 360 azimuth angles.